Karaoke Reservation System for Room and Customer Management Optimization - Siregar, Ridho Fadlan Fahira; Gading, Rafli Arya; Raya, Fathul Hady (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
This research discusses the development of a desktop-based karaoke reservation system designed to improve operational efficiency in room management and customer data processing. The system was developed in response to various problems commonly found in traditional karaoke business operations, such as manual data recording that is prone to human error, inefficiencies in managing room schedules, delays in administrative services, and the absence of real-time monitoring of room availability. These issues often lead to scheduling conflicts, inaccurate billing, and reduced customer satisfaction. The research methodology consisted of several stages, including user needs analysis to identify system requirements, interface design to ensure ease of use, system implementation using Java Swing as the programming framework, database development using MySQL, and functional testing to evaluate system performance. The system integrates reservation management, customer data recording, room status monitoring, and automatic cost calculation based on usage duration. The results show that the developed system significantly improves the speed and accuracy of the reservation process. Schedule conflicts can be minimized through structured room availability management, while customer data is recorded more accurately and systematically. The real-time display of room status allows administrators to monitor room usage efficiently, supporting better decision-making. Additionally, the automatic pricing feature ensures consistency and transparency in cost calculations, reducing errors caused by manual billing. In conclusion, the desktop-based karaoke reservation system proves to be an effective solution for optimizing karaoke business operations.